Инновации в видовой системе русского языка - Климонов, Владимир (Studia Rossica Posnaniensia, 2015)
Grammatical and lexical changes in the aspect system of Russian are investigated within the framework of the theory of Natural Grammar. It is claimed that the direction of morphological changes is determined by a limited number of typologically relevant markedness principles or laws of preferences. These principles explain the attested diachrony of grammatical changes in the aspect system of Russian and allow one to predict the direction of development of the aspect system.